Effect of Proportion of Jack bean Flour, Tapioca Flour, and Corn Starch on the Nutrition of Instant Milkfish Crabstick - Ismiyatul Finani, Nadira; Rosida, Dedin Finatsiyatul; Yusuf Trisna P, Andre (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Jack bean (Canavalia ensiformis) is a local legume with a high protein content, offering potential as an alternative to wheat flour. The addition of tapioca starch and corn starch in fish jelly products aims to improve texture and enhance gel strength. This study aims to determine the optimal combination of jack bean flour, tapioca flour, and corn starch proportions, along with the appropriate carrageenan concentration, to produce high-quality instant crab sticks. A completely randomized design (CRD) was used with two factors: the proportion of jack bean flour, tapioca flour, and corn starch (10:70:20, 20:50:30, and 30:30:40) and the concentration of carrageenan (1.5%, 2.5%, and 3.5% w/b). Data were analyzed using Two-Way ANOVA at a 5% significance level, followed by DMRT at 5% if significant interactions were found. The best formulation was obtained using a proportion of 20% jack bean flour, 50% tapioca flour, and 30% corn starch, combined with 2.5% carrageenan. This formulation yielded a moisture content of 11.05%, ash content of 3.67%, fat content of 4.84%, protein content of 31.89%, and carbohydrate content of 48.47%. These findings highlight the potential of jack bean flour as a functional ingredient in the development of high-protein, wheat-free crabsticks. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-Being.SDG 9: Industry, Innovation, and Infrastructure.SDG 12: Responsible Consumption and ProductionSDG 13: Climate Action.